Prototype of a simulation framework for georeferenced large-scale dynamic simulations of district energy systems. (15th October 2019) - Nageler, P.; Heimrath, R.; Mach, T.; Hochenauer, C.
Highlights: Prototype for district heating network modelling and result visualization. Co-simulation of buildings, district heating network, and heat generation plant. Large-scale simulation of a dynamic district heating network. Animation of temperature propagation in a district heating network. Evaluation of the supply reliability in failure scenarios. Abstract: With the increasing complexity of district energy systems, both researchers and enterprises require ever more complex modelling and simulation methods. This has resulted in the need for new approaches that can be taken to create large-scale simulations as well as new methods to clearly visualize their dynamic simulation results. This study presents a prototype of a simulation framework for large-scale simulations of district energy systems that offers three main advantages compared to the state of the art: (i) scalable simulation models are made possible; (ii) a novel heating network model generation tool was developed that can be used to create models for the IDA ICE simulation environment; and (iii) the dynamic results of the simulation of the heating network and the buildings can be visualized as animations in QGIS, which makes it possible to clearly visualize the superimposed result layers of the buildings and the network. The prototype was tested in a two-part case study. In the first part of the study, the extent of the district heating network model size was examined, and decoupling methods were applied to 1531 customers. The second part of the study involved a failure scenario, which evaluated the effects of a malfunction at the heat generation plant on the 469 connected buildings. One significant finding was that the temperature progression in the network reacts comparatively quickly, while the room air temperature in well-insulated buildings with larger thermal storage masses cool more slowly. Another finding was that IDA ICE allows fast and accurate simulations with up to 8200 customers or 36, 000 pipes in meshed heating networks without parallelization techniques.